ANALYSIS OF MINIMUM COMPETENCY ASSESSMENT (AKM) QUESTIONS IN MADRASAH ASSESSMENT IN INDONESIAN LANGUAGE SUBJECT CLASS VI MIS NURUL HUDA BENGKULU CITY - Mustofa, Ahmad; Muktadir, Abdul; Widi Winarni, Endang (UNIB Press, 2025)
This research aims to describe the content elements, cognitive processes and context of AKM questions in madrasa assessments for class VI Indonesian language subjects for the 2021/2022 and 2022/2023 MIS Nurul Huda Bengkulu City academic years. This type of research is mixed methods research. The subjects of this research were class VI students of MIS Nurul Huda, Bengkulu City. The objects in this research are content elements, cognitive processes, and the context of reading literacy, student responses to items in the madrasa assessment for Indonesian language The research instrument is a document in the form of a sheet of analysis results of content elements, cognitive processes and the context of reading literacy. content, cognitive processes, and reading literacy contexts are analyzed and calculated according to the rater's agreement. The results of the research show that: (1) The highest content element for the 2021/2022 AKM questions is information text with 22 questions and the highest content element for AKM 2022/2023 questions is information text with 28 questions; (2) The highest cognitive process element for the 2021/2022 AKM questions is finding information on 28 questions and the highest cognitive process element for the 2022/2023 AKM questions is finding information on 27 questions; (3) The highest context element for the 2021/2022 AKM questions is personal with 22 questions and the highest context element for the 2022/2023 AKM questions is scientific with 15 questions.